PERBANDINGAN PERLAKUAN PAJAK DAN ZAKAT PADA PRODUK KEUANGAN ISLAMI MUDHARABAH DAN MURABAHAH - Rismawati - Rismawati; Supriadi - (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
This paper aims to describe the past and present tax and zakat obligations imposed on each Muslim as two different obligations through a literature review. Taxes are levied by the government on every citizen including Muslims with the aim of assisting the government in financing the state. While zakat is paid by Muslims based on religious obligations aimed at increasing the devotion of the Ummah, reducing poverty and increasing solidarity and building economic sustainability. Using  a descriptive method, this study found that in contemporary Islamic economics, zakat is used as a tool to improve the economy with an interest-free loan system (qardul hasan). Mudharabah and Murabahah are both Islamic financial products designed by considering aspects of sharia compliance, including the fulfillment of zakat obligations. The basic principle of zakat in Islam is the obligation to give a portion of wealth to those who deserve it. Meanwhile, the imposition of taxes on Islamic financial products has the same purpose as the imposition of taxes on conventional financial products, namely to finance government spending in providing public services to the public. The payment of zakat through official institutions can be submitted as a tax deduction, so that the tax functions as the main source of state revenue and is used entirely for the benefit of the people in line with the purpose of zakat payment in Islam.